PROFIL PENYIMPANAN OBAT DI PUSKESMAS TAMALANREA JAYA KOTA MAKASSAR - Nurlina Nurlina; Bayu Putra; Arnilasari Arnilasari (As-Syifaa Jurnal Farmasi, 2022)
Storage of pharmaceutical dosage forms and single-use medical devices is a regulation of the pharmaceutical dosage forms received to be safe (not to lost), to avoid physical and chemical damage and the quality remains guaranteed, in accordance with the requirements set. This research aimed to find out the profile of drug storage in Tamalanrea Jaya subdistrict community Health Center in Makassar City. This research was a descriptive study. The informant in this study was the Head of Pharmaceutical Installation of Tamalanrea Jaya Makassar Health Center. Data was collected through in-depth interviews and observations. The results of the study stated that infrastructure facilities meeting the prevailing regulation in drug storage warehouses according to conformity percentage were 81%. The organisation of drugs in the storage warehouse of community Health Center Pharmaceutical Installation by 85% was carried out based on the standards. The card stock of the drug was fulfilled, which the percentage of conformity indicated 100%.